Methodological factors in determining risk of dementia after transient ischemic attack and stroke - Pendlebury, S; Chen, P; Welch, S; Cuthbertson, F; Wharton, R; Mehta, Z; Rothwell, P (American Heart Association, 2015)
BACKGROUND AND PURPOSE: Cognitive outcomes in cohorts and trials are often based only on face-to-face clinic assessment. However, cognitive impairment is strongly associated with increased morbidity and mortality, leading to substantial loss to clinic follow-up. In the absence of previous population-based data, we determined the effect of such attrition on measured risk of dementia after transient ischemic attack and stroke. METHODS: Patients with transient ischemic attack or stroke prospectively recruited (2002-2007) into the Oxford Vascular (OXVASC) study had baseline clinical/cognitive assessment and follow-up to 2014. Dementia was diagnosed through face-to-face clinic interview, supplemented by home visits and telephone assessment in patients unable to attend clinic and by hand-searching of primary care records in uncontactable patients. RESULTS: Of 1236 patients (mean age/SD, 75.2/12.1 years; 582 men), 527 (43%) died by 5-year follow-up. Follow-up assessment rates (study clinic, home visit, or telephone) of survivors were 947 in 1026 (92%), 857 in 958 (89%), 792 in 915 (87%), and 567 in 673 (84%) at 1, 6, 12 months and 5 years. Dementia developed in 260 patients, of whom 110 (42%; n=50 primary care records, n=49 home visit, and n=11 telephone follow-up) had not been available for face-to-face clinic follow-up at the time of diagnosis. The 5-year cumulative incidence of postevent dementia was 29% (26%-32%) overall but was only 17% (14% to 19%) in clinic assessed versus 45% (39%-51%) in nonclinic-assessed patients (P difference<0.001). CONCLUSIONS: Exclusion of patients unavailable for clinic follow-up reduces the measured risk of postevent dementia. Use of multiple follow-up methods, including home visits, telephone assessments, and consent, to access primary care records substantially increases ascertainment of longer-term dementia outcomes.